1997
DOI: 10.1093/oxfordjournals.aje.a009330
|View full text |Cite
|
Sign up to set email alerts
|

Measles Incidence, Case Fatality, and Delayed Mortality in Children with or without Vitamin A Supplementation in Rural Ghana

Abstract: Data on measles incidence, acute case fatality, and delayed mortality were collected on 25,443 children aged 0-95 months during the course of a community-based, double-blind, placebo-controlled, randomized trial of vitamin A supplementation in rural, northern Ghana between 1989 and 1991. Measles vaccine coverage in these children was 48%. The overall estimated measles incidence rate was 24.3 per 1,000 child-years, and acute case fatality was 15.7%. There was not significantly increased mortality in survivors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
(29 reference statements)
2
40
3
Order By: Relevance
“…The study conducted by Dollimer N et al has shown overall estimated measles incidence rate 24.3 per 1,000 child-years in rural Ghana. 16 The vaccine coverage rate was found 64.624% in the present study in 9-59 age group and similar kind of study conducted in Ahmedabad by Bhagyalaxmi A et al 11 has shown 59.88% coverage rate of vaccination of measles. A coverage rate of measles vaccination in 12-23 age group children was found 44.4% and Desai VK et al…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The study conducted by Dollimer N et al has shown overall estimated measles incidence rate 24.3 per 1,000 child-years in rural Ghana. 16 The vaccine coverage rate was found 64.624% in the present study in 9-59 age group and similar kind of study conducted in Ahmedabad by Bhagyalaxmi A et al 11 has shown 59.88% coverage rate of vaccination of measles. A coverage rate of measles vaccination in 12-23 age group children was found 44.4% and Desai VK et al…”
Section: Discussionsupporting
confidence: 80%
“…A study conducted by Dollimer N et al 16 in rural Ghana has shown 48% coverage of measles vaccine. The incidence studies carried out in Ahmedabad, Rajkot and Jamnagar revealed overall vaccination coverage between 46.7 to 58.9% in 1999.…”
Section: Discussionmentioning
confidence: 98%
“…The causes of these differences in clinical outcome between the developed and the developing world are not well understood. Several hypotheses have been put forward such as the dose rate of infection [11], immunological challenge by other infections, vitamin status, and strain differences [12]. However, at present, none of these offers a satisfactory explanation for the striking differences in the clinical symptoms manifested in infected children.…”
Section: Introductionmentioning
confidence: 99%
“…Except for some rare isolates from Cameroon and Gabon from the mid-1980s and Gambian isolates in the 1990s, no MV field strains have ever been investigated in northern and central Africa (Taylor et al, 1991 ;Rota et al, 1994 b ;Outlaw et al, 1997). Yet, this may well be the global region with the highest measles morbidity and mortality (Dollimore et al, 1997 ;WHO, 1996). In Nigeria, for instance, measles is endemic and the death toll is exceedingly high in young infants (Byass et al, 1995 ;O.…”
Section: Introductionmentioning
confidence: 99%